1998
DOI: 10.1007/s004220050492
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the electroencephalographic activity during the Necker cube reversals by means of the wavelet transform

Abstract: In previous studies, a perceptual switching related potential was obtained during the observation of a multistable dynamic reversal pattern, where the averaging of the single responses was triggered by subjects pressing a button. The present methodological study aims to increase the signal quality of perceptual switching related potentials considering the dependence of the measurement method on the reaction time of the subject, which may vary significantly during a session, leading to low-amplitude waveform in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…A reversal-related delta component, by its functional and topographical similarity to the P300, was interpreted as reflecting the recognition of the perceptual change (BasarEroglu, et al, 1993;Isoglu-Alkac et al, 1998;Mathes, Strüber, Stadler, & Basar-Eroglu, 2006;Strüber & Herrmann, 2002). Top-down processing during multistable perception is indicated by the frontal maximum of theta Nakatani & van Leeuwen, 2005) and gamma activity (Basar-Eroglu, Strüber, Kruse, et al, 1996;Strüber, et al, 2000;Strüber, et al, 2001).…”
Section: Future Prospects: Disturbances Of the Interplay Between Diffmentioning
confidence: 98%
“…A reversal-related delta component, by its functional and topographical similarity to the P300, was interpreted as reflecting the recognition of the perceptual change (BasarEroglu, et al, 1993;Isoglu-Alkac et al, 1998;Mathes, Strüber, Stadler, & Basar-Eroglu, 2006;Strüber & Herrmann, 2002). Top-down processing during multistable perception is indicated by the frontal maximum of theta Nakatani & van Leeuwen, 2005) and gamma activity (Basar-Eroglu, Strüber, Kruse, et al, 1996;Strüber, et al, 2000;Strüber, et al, 2001).…”
Section: Future Prospects: Disturbances Of the Interplay Between Diffmentioning
confidence: 98%
“…In this context, the timing of the involved neural mechanisms is of special importance, which can be analyzed by means of EEG or MEG providing high temporal resolution. Previous ERP studies on multistable perception found a late P300-like component induced by the figure reversal (O'Donnell et al, 1988;Basar-Eroglu et al, 1993;Isoglu-Alkac et al, 1998Strü ber et al, 2001;Strü ber and Herrmann, 2002), which indicates the conscious 0167-8760/$ -see front matter D 2005 Elsevier B.V. All rights reserved. doi:10.1016/j.ijpsycho.2005.05.002 recognition of perceptual change and, therefore, the closure of the reversal process.…”
Section: Introductionmentioning
confidence: 98%
“…These findings may help to explain previous contradictory results of respiration effects on RT and may guide future research on cognitive enhancement strategies. In our recent studies (Isoglu-Alkac et al, 1998, we have shown the gradual decrease of alpha activity, as well as increased delta and gamma activity during Necker-Cube reversals. We suggested that gamma activity plays a role in attentional top -down processing, whereas desynchronized alpha might be related to bottom -up processes.…”
Section: Do the Recognition Potential And The Early Repetition Effectmentioning
confidence: 96%
“…The 40-Hz recordings were collected to provide additional information to that obtained by Bertrand et al (1990), Butler et al (1996, 1998), Fisher et al (1996 and Guérit et al (1998) who monitored coma states and recorded evoked potentials (EP) in patients with prolonged coma. Fischer et al (1999), showed that their late cortical recordings differed from healthy subjects in terms of waveform, latencies and amplitudes.…”
Section: -Hz Responses During Light Coma In Chi Patientsmentioning
confidence: 99%